The making and unmaking of whiteness - Brander Rasmussen, Birgit, 1968-; Klinenberg, Eric; Nexica, Irene J.; Wray, Matt, 1964- (E-Duke books scholarly collection., 2001)
A collection of new essays in race theory, drawn from the 4/97 Berkeley conference.